The living Christ and the four Gospels - Dale, Robert William, 1829-1895 (London, UK Hodder and Stoughton, 1905)
Includes bibliographical references.
Keywords: Bible. N.T. Gospels -- criticism, interpretation, etc; Jesus Christ -- person and offices